Gait Analysis and Knee Kinematics in Patients with Anterior Cruciate Ligament Rupture: Before and After Reconstruction - Dmitry Skvortsov; Sergey Kaurkin; Alexander Akhpashev; Aljona Altukhova; Alexander Troitskiy; Nikolay Zagorodniy (Applied Sciences, 2020)
The objective of the study was to evaluate the clinical, functional, and biomechanical symptoms in patients with anterior cruciate ligament (ACL) rupture before and after ACL reconstruction. The study enrolled 20 patients and 20 healthy subjects as controls. Walking biomechanics was assessed at three time points: before surgery and three months and a year or more after surgical reconstruction. Impact loads on both sides differed significantly from the respective values before surgery (p<0.05). Walking cycle duration decreased with time after surgery. On both sides (affected and unaffected), hip movement amplitudes were significantly smaller than in control (p<0.05). They remained so in the follow-up periods after the reconstruction. Before ACL reconstruction, the amplitude of the main flexion of the knee was significantly reduced both on the affected and unaffected sides. The amplitude gradually increased after the reconstruction, and a year post-surgery, it reached, on the operated side, the same values as in the control group. Complete functional recovery of the knee joint was not achieved within a year after the ACL surgical reconstruction. The remaining changes, however, were not clinically pronounced and could only be detected by instrumental gait analysis. The compensatory processes developed bilaterally, in both the hip and knee joints.